2003
DOI: 10.1007/s00415-003-0239-5
|View full text |Cite
|
Sign up to set email alerts
|

Driving in Parkinson?s disease?a health hazard?

Abstract: Further prospective community-based well designed studies on accident risk in PD patients are needed to provide evidence based driving recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…5,[11][12][13]16 Epidemiologic data, however, are not well-established concerning crash rates in PD. [18][19][20] A retrospective survey study found that patients with Hoehn & Yahr (H&Y) stages 2 and 3 had a significantly higher crash risk compared to healthy controls. However, there was no evidence of increased crash risk among patients in H&Y stage 1.…”
mentioning
confidence: 99%
“…5,[11][12][13]16 Epidemiologic data, however, are not well-established concerning crash rates in PD. [18][19][20] A retrospective survey study found that patients with Hoehn & Yahr (H&Y) stages 2 and 3 had a significantly higher crash risk compared to healthy controls. However, there was no evidence of increased crash risk among patients in H&Y stage 1.…”
mentioning
confidence: 99%
“…Although many studies showed decreased driving performances in PD patients, there is no clear evidence on real risk of crashes in this population [20,21]. Some authors have shown an increased crash rate in driving simulator studies [13,22] or in retrospective studies, especially those in whom the disease is severe [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with neurologically healthy drivers, those with PD show greater impairment on route-finding tasks and landmark and traffic sign identification tasks (mild to moderate PD only; Uc et al, 2006bUc et al, , 2007. Yet, PD patients are not more prone to cause crashes than the rest of the population (Homann et al, 2003).…”
mentioning
confidence: 99%